Analisis Proses Pengambilan Keputusan oleh Pemimpin dalam Menciptakan Komitmen Organisasi - Suandika, I Gede Krisna Surya; Gorda, A.A.N. Oka Suryadinatha (Universitas Proklamasi 45, 2024)
The purpose of this research is to analyze the way leaders make decisions to implement an organization's commitment. The research method used is a qualitative research method and a social construction phenomenology approach which interpretatively aims to determine the implementation of a leadership decision in an organization. The research location was at BPR Pusaka examining six informants consisting of employees and leaders. Data collection techniques were carried out using interviews, observation, and documentation at the research location. Data analysis uses triangulation of sources, techniques, and time. The results of this research found that in determining policies, the role of leaders is very necessary in designing structured Terms of Reference to achieve good results to achieve the goals of an organization. The application of fair and effective leadership and decision-making is very necessary so as not to give rise to a tendency to overthink or worry which can lead to poor communication.